An analysis of the relationships of the inventoried occupational interests to some socio-psychological factors and its congruence with the expressed career choices of Maryknoll high school seniors, Schoolyear 1975-76 - Amora, Doroteo O. (Animo Repository, 1976)
This study aims to find out if personality traits as measured by the High School Personality Questionnaire, academic achievement, and socio-economic status relate significantly to Occupational Interest Inventory (OII). It also aims to determine whether expressed choices correspond to inventoried interests, and to identify the characteristics, specifically academic achievement, personality traits, and socio-economic status which are common to students whose expressed and inventoried interests matched. This study employed the descriptive method of research. The subjects of the study were 71 male and female high school students of Maryknoll High School of Lupon, Davao, Oriental, enrolled for the schoolyear 1975-76. The instruments used were the Occupational Interest Inventory and the High School Personality Questionnaire. Castaneda's (1972) socio-economic survey questionnaire was adopted and the grade point averages were obtained from the school records. The Pearson r, chi-square test, and the test of means on independent samples were the statistical techniques employed to determine the direction and degree of relationship between variables. It was found that personality traits, socio-economic status, and academic achievement were relevant to the vocational behavior of the subjects. A generally low and negligible relationship between the subjects' interests and personality traits existed. Also, there was found to be a congruence between expressed and inventoried choices of the subjects. To help the students define and redefine their occupational roles realistically, being aware of the conditions, manpower demands, and projections of the world of work, it was concluded that an organized vocational guidance information service was called for. It was deemed important that high school students be aware of their personality patterns because such awareness contributed to the narrowing down of vocational choices. It was also important that in vocational guidance and counseling, consideration be given to the reality constraints or contingencies of the subjects. To counsel students on the trait and factor basis alone without relating it to the realities of parents, financial resources, and values would be unrealistic. As such, environmental factors can not be overlooked.